Prognostic Value of Classifying Parapharyngeal Extension in Nasopharyngeal Carcinoma Based on Magnetic Resonance Imaging. (26th March 2015) - Zhang, Guo-Yi; Huang, Ying; Hu, Xue-Feng; Chen, Xiang-Ping; Xu, Tao; Liu, Li-Zhi; Wei, Wei-Hong; Huang, Guo-Sen; Zhou, Miao-Miao; Huang, Ze-Li; Wang, Yue-Jian
Abstract : Purpose . To subclassify parapharyngeal extension in nasopharyngeal carcinoma (NPC) and investigate its prognostic value and staging categories based on magnetic resonance imaging (MRI). Methods and Materials . Data from 1504 consecutive NPC patients treated with definitive-intent radiotherapy were analyzed retrospectively. Sites of parapharyngeal extension were defined by MRI. Overall survival (OS), local relapse-free survival (LRFS), and distant metastasis-free survival (DMFS) were calculated by the Kaplan-Meier method and compared with the log-rank test. Hazard consistency and hazard discrimination were determined by multivariate analysis with Cox proportional hazards models. Results . 1104 patients (73.4%) had parapharyngeal extension; 1.7–63.8% had involvement of various anatomic sites. The hazard ratio for death was significantly higher with extensive parapharyngeal extension (lateral pterygoid muscle of masticator space and beyond or parotid space) than with mild extension (medial pterygoid muscle of masticator space, or carotid, prestyloid, and prevertebral or retropharyngeal space). OS, LRFS, and DMFS with extensive parapharyngeal extension were similar to those in T4 disease; OS, LRFS, and DMFS with mild parapharyngeal extension were significantly higher than in those T3 disease (all P ≤ 0.015). Conclusions . Parapharyngeal extension in NPC should be subclassified as mild or extensive, which should be regarded as stages T2 and T4 diseases, respectively.